THE INFLUENCE OF LIFE EXPECTANCY, AVERAGE LENGTH OF SCHOOL AND EXPECTATION OF LENGTH OF SCHOOL ON HUMAN DEVELOPMENT INDEX IN BINJAI CITY - Siti Alifah Handayani; Lubis, Nasrullah Hidayat; Dhea Amanda; Syarifah; Muhammad Bagas Ardhana; Tiara Posma Udur Hutapea (Universitas Negeri Medan, 2024)
This research aims to analyze the influence of life expectancy, average length of schooling, and expected length of schooling on the Human Development Index (HDI) in Binjai City, Indonesia. Using a quantitative approach and secondary data from the Central Statistics Agency (BPS) for the period 2010 to 2023, regression analysis shows that these three variables have a significant influence on HDI, with an Adjusted R Square of 0.995, which means 99.5% of the variation in HDI can be explained by these variables. the. The F test results showed a significant regression model (F = 865.744, Sig. = 0.000), while the t test confirmed that life expectancy (t = 6,139), average years of schooling (t = 8,478), and expected years of schooling (t = 6,254) contributes positively to HDI. These findings emphasize the importance of health and education in improving people's quality of life. This research recommends increasing access to education and health services as a strategic step to increase HDI and community welfare in Binjai City. It is hoped that the research results can become a reference for policy makers in designing effective programs for human development in the region